Evaluating Deficiency of Vitamin B12 and Risk Factors in Healthy Infants - Riffat Naeem, Farah Rafique, Hamail Amin, Andleeb Badar, Hira Sohail, Farhat Ijaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The deficiency of vitamin b12 is highly extensive within the developed countries and is often found to remain undiagnosed within these populations. the main feature within infants suffering from vitamin b12 deficiency is altered neurological development and generalized growth. Effects of vitamin b12 deficiency on the brain can be prevented. To avoid these morbidities and mortality associated with vitamin b12 deficiency it is pivotal for clinicians to understand what other risk factors are associated with a deficiency within the infant population of developing countries. Materials and methods: This cross-sectional study was conducted on 82 healthy infants for the assessment of Vitamin B12 at Pediatric Department of LGH, Lahore from March 2021 to August 2021. Participants were selected who were healthy. After recruitment, participants underwent hematological and biochemical indices analysis. Hemoglobin, serum vitamin b12, homocysteine and methylmalonic acid were different parameters measured. Maternal vitamin b12 deficiency was investigated along with risk factor vitamin b12 deficiency in healthy infants. Results: A total of 82 recruited participants were selected after screening and meeting the recruitment criteria. After assessment of hematological data, anemia was diagnosed in 67.82% of infants (n=56). The breakdown of the anemic population showed that the male population was predominant with 58.2% affected males and 41.8% affected females. Decreased levels of plasma vitamin b12 concentration were documented in 22% of the population with a total number of 18 participants (male: 11, female: 7). Increased levels of homocysteinemia were documented in 49.1% of infants with n=40. Increased levels of methylmalonic acid were appreciated in all infants. As defined by previous criteria, the diagnosis of vitamin b12 deficiency was appreciated in 30 infants with a percentage of 38%. Furthermore, an assessment of folate deficiency showed that 8 out of 82 participants had concurrent folate deficiency in red cells with a percentile prevalence of 9.7%. maternal vitamin b12 deficiency was considered as risk factor for infant vitamin b12 deficiency Conclusion: The prevalence of vitamin b12 deficiency in healthy infants is significantly high in developing and underdeveloped countries. Vitamin b12 deficiency cooccurs with anemia and other variation of biological markers. The study concluded that among the various risk factors that may predispose an infant to vitamin b12 deficiency, maternal b12 deficiency remains the highest appreciated risk factor.